The measurement of yearly C-, N- and CH4 balance in characteristic Hungarian wetland ecosystems. Preliminary results - Czóbel, Szilárd (Acta Biologica Szegediensis, 2008)
Wetlands macro-vegetation plays an important role in bio-filtration processes. Global warming is anticipated to modify many water ecosystems of the Earth. In submerged plants especially, the photosynthetic rate may be limited by a low availability of dissolved inorganic carbon. Our study demonstrates one of the first results for stand Net Ecosystem CO2 Exchange (NEE) rates for characteristic European aquatic vegetation types based on in situ measurements. To measure NEE of aquatic (floating and submerged) associations at stand level a self-developed, portable, floating open chamber system (d=60cm) was used. Soil fluxes of methane and nitrous oxide were also determined for different wetland ecosystems representing a moisture gradient in Bodrogköz wetlands. As the direction of N2O and methane fluxes (emission or uptake) depends on the soil water content characteristics bi-directional fluxes were observed. Our study demonstrated, based on production analyses and NEE measurements, that from the carbon-dioxide point of view the lakes and streams characterized by significant living plant biomass can be counted as a carbon sequester on a yearly horizon due to the intensive carbon sequestration of submerged and floating vegetations. The majority of examined fluxes and parameters varied considerably among the studied years.